Effects of cord blood vitamin D levels on the risk of neonatal sepsis in premature infants - Birgul Say; Nurdan Uras; Suzan Sahin; Halil Degirmencioglu; Serife Suna Oguz; Fuat Emre Canpolat (Korean Pediatric Society, 2017)
PurposeVitamin D plays a key role in immune function. Vitamin D deficiency may play a role in the pathogenesis of infections, and low levels of circulating vitamin D are strongly associated with infectious diseases. In this study, we aimed to evaluate the effects of low vitamin D levels in cord blood on neonatal sepsis in preterm infants.MethodsOne hundred seventeen premature infants with gestational age of <37 weeks were enrolled. In the present study, severe vitamin D deficiency (group 1) was defined as a 25-hydroxyvitamin D (25(OH)D) concentration <5 ng/mL; vitamin D insufficiency (group 2), 25(OH)D concentration ≥5 ng/mL and <15 ng/mL; and vitamin D sufficiency (group 3), 25(OH)D concentration ≥15 ng/mL.ResultsSixty-three percent of the infants had deficient levels of cord blood vitamin D (group 1), 24% had insufficient levels (group 2), and 13% were found to have sufficient levels (group 3). The rate of neonatal sepsis was higher in group 2 than in groups 1 and 3.ConclusionThere was no significant relationship between the cord blood vitamin D levels and the risk of neonatal sepsis in premature infants.